Bilateral Simultaneous Tibial Tubercle Avulsion in an Adolescent Football Player with Previous Bilateral Osgood–Schlatter Disease - Jaime Dalla Rosa Nogales; José Juan Nogales Zafra (Case Reports in Orthopedics)
Tibial tubercle avulsion fractures are a very uncommon injury, accounting between 0.4 and 2.7% of all epiphyseal injuries. Bilateral lesions are extremely rare with only 20 cases described in the literature. They occur more frequently in male adolescents and during sport activities that require jumping and sprinting, such as football or basketball. We report the case of a 13-year-old boy who sustained simultaneous bilateral tibial avulsion fractures on the background of a previous conservatively managed bilateral Osgood–Schlatter disease.